Internet Addiction And Procrastination In University Students In Lima: The Mediating Role Of Anxiety - Valderrama Puscan, Marlon Walter; Palacios Montes, Coraima Nayelli; Velasquez Salinas, Mayra Alejandra (LACCEI, 2025)
The present research aimed to determine whether Internet addiction predicts academic procrastination when mediated by anxiety in college students. The thesis had a quantitative approach, basic, non-experimental design, cross-sectional and predictive level. The participants were 378 male and female university students ranging from 16 to 55 years old. The Internet Addiction Test, the Academic Procrastination Scale and the Trait-State Anxiety Inventory were used for this study. The results indicated that the Indirect Effect of anxiety on the relationship between the independent and dependent variable, obtained a confidence interval between .002 and .026, which is statistically significant. It was concluded that internet addiction predicts anxiety, encouraging college students to procrastinate.